The contextualization of educational values: Symbolic forms in the interaction of learning process in IAIN Palopo - Sukirman Sukirman; Makmur Makmur (Fakultas Sastra Universitas Negeri Malang, 2021)
The contextualization of educational values: Symbolic forms in the interaction of learning process in IAIN PalopoThis study describes aspects of symbolic forms that take place in the interaction of speech acts in learning process at IAIN Palopo, namely the formation of patterns of ideological transformation and character in learning process. Furthermore, this study aims to uncover the values of education expressed in the context of learning. The values are expressed through ideology and critical ideas are represented in symbolic forms. This study used Grounded Theory (GT) and ethnographic approach as it explored interaction behavior in learning. The research subjects were lecturers and students through which utterances containing symbolic forms as primary data sources were elicited via audiovisual recording. Data collection techniques used non-participatory observation and documents, while data analysis techniques employed identification, data reduction, interpretation, presentation, explanation, and conclusions respectively. This current study found some aspects of the continuity of ideology and character in the learning interaction discourse at IAIN Palopo transformed using the patterns of (1) interactions/commands, (2) interrogatives/questions, (3) warnings/advising, (4) comparisons, (5) flexibility, (6) flattery/praise, (7) reinforcement, (8) discipline/orderliness, (9) persuasive/promoting, (10) flexibility/acceptance, and (11) participatory. Here, the patterns function as a strategy for the speaker to express ideology and character to express educational values, such as competence, self-motivation, order, creativity, skills, personality, harmonious attitude, and togetherness that is developed through the context of the learning process. Keywords: contextualization, educational values, symbolic forms, learning processKontekstualisasi nilai pendidikan: Bentuk simbolik dalam interaksi proses pembelajaran di IAIN PalopoPenelitian ini mendeskripsikan aspek bentuk simbolik yang berlangsung dalam interaksi tindak tutur pembelajaran di IAIN Palopo, yaitu pembentukan pola transformasi ideologi dan karakter berlangsung dalam pembelajaran. Selanjutnya, penelitian ini bertujuan mengungkap nilai-nilai pendidikan yang dinyatakan dalam kontekstualisasi pembelajaran. Nilai tersebut dinyatakan melalui ideologi dan ide kritis direpresentasikan dalam bentuk simbolik. Penelitian ini menggunakan jenis grounded theory (GT) dan etnografi karena kajiannya didasarkan pada perilaku interaksi pembelajaran. Selanjutnya, digunakan pendekatan kualitatif bersifat alamiah. Subjek penelitian, yaitu dosen dan mahasiswa sebagai sumber data primer berupa tuturan (teks lisan) yang mengandung bentuk simbolik disadur melalui alat perekam (handycam). Teknik pengumpulan data yang digunakan observasi (nonpartisipatif), dan dokumen, sedangkan teknik analisis data, yaitu secara bertahap digunakan identifikasi, reduksi data, interpretasi, penyajian, eksplanasi, dan simpulan. Berdasarkan hasil analisis dan pembahasan ditemukan aspek keberlangsungan ideologi dan karakter dalam wacana interaksi pembelajaran di IAIN Palopo ditransformasi dengan menggunakan pola (1) interaksi/ perintah, (2) interogatif/ pertanyaan, (3) peringatan/ menasihati, (4) perbandingan, (5) keluwesan/ pelenturan, (6) sanjungan/ pujian, (7) penguatan, (8) kedisiplinan/ keteraturan, (9) persuasif/ mempromosikan, (10) fleksibilitas/ penerimaan, dan (11) partisipatif. Pola tersebut menjadi strategi penutur menyatakan ideologi dan karakter untuk mengungkap nilai-nilai pendidikan, seperti kompetensi, motivasi diri, keteraturan, kreativitas, keterampilan, kepribadian, sikap harmonis, kebersamaan yang terbangun melalui proses kontekstualisasi ruang pembelajaran.Kata Kunci: kontekstualisasi, nilai pendidikan, bentuk simbolik, interaksi belajar mengajar